Motives and an attempt to measure them in sports - Palaima, J. (Psichologija, 1968)
Man is driven by the need to act, but it only becomes a motive when he realizes the objects that could meet that need. Objects can be material and ideal, things and thoughts, feelings and moral values.Because of the inherent need for internal communication fundamental human mental powers mobilize —both intellect and emotion—fulfilling the need to find objects. Those powers sort of embody the object: the cognitive process and approach (relationship), on which the object acquires a certain meaning for humans is realized therein. Intelligence and emotion—the cognitive and emotional—these are the components of motive, and its business can be called its motivational side, which is the root of people's actions, behavior, and power. Willpower is basically a motive force, and a strong-willed man is primarily a highly motivated person.We tried to use a real world experiment to help determine the comparative strength of moral motives (a sense of collectivity) in a basketball game. We used assignment to the first or second string as a point of comparison (encouraging personal motive) as well as the team's prestige (encouraging moral motive) The players were informed ahead of time that the results and personal stats in the first game will be published while the second game they will not, only team stats will be announced; this condition was the main way to determine moral motive force. The findings of the experimental data regarding the degree of development of moral reasoning of the players (20 young basketball players) essentially matched the coaches' opinion.In a similar experiment it would be appropriate to investigate individual athletes, too, as better athletic achievements are generally achieved in team competition, yet they do not always show contestants' stronger moral reasoning: in team contests the athletes can do more to promote individualistic motives, too, because personal results are published.
Keywords: sports; motivation; motives; sports motivation